Epidemiologic and microbiologic evaluation of nosocomial infections associated with Candida spp in children: A multicenter study from Istanbul, Turkey - KEPENEKLİ KADAYİFCİ, EDA (MOSBY-ELSEVIER, 2016)
Background: The purpose of this study was to establish species distribution of Candida isolates from pediatric patients in Istanbul, Turkey, and to determine risk factors associated with nosocomial Candida infections. Methods: This study was conducted between June 2013 and June 2014 by participation of 7 medical centers in Istanbul. Candida spp strains isolated from the clinical specimens of pediatric patients were included. Clinical features were recorded on a standardized data collection sheet. Results: A total of 134 systemic Candida infections were identified in 134 patients. The patients were admitted in pediatric and neonatal intensive care units (41.8% and 9.7%, respectively) and in pediatric wards (48.5%). Candida albicans was the most prevalent species (47%), followed by Candida parapsilosis (13.4%), Candida tropicalis (8.2%), Candida glabrata (4.5%), Candida lusitaniae (3.7%), Candida kefyr (2.2%), Candida guilliermondii (1.5%), Candida dubliniensis (0.7%), and Candida krusei (0.7%). Types of Candida infections were candidemia (50.7%), urinary tract infection (33.6%), surgical site infection (4.5%), central nervous system infection (3.7%), catheter infection (3.7%), and intra-abdominal infection (3.7%). In multivariate analysis, younger age (1-24 months) and detection of non-albicans Candida spp was found to be risk factors associated with candidemia (P = 0.040; odds ratio [OR], 4.1; 95% confidence interval [CI], 1.06-15.86; and P = 0.02; OR, 2.4; 95% CI, 1.10-5.53, respectively). Conclusions: This study provides an update for the epidemiology of nosocomial Candida infections in Istanbul, which is important for the management of patients and implementation of appropriate infection control measures. (C) 2016 Association for Professionals in Infection Control and Epidemiology, Inc. Published by Elsevier Inc. All rights reserved.
Keywords: Systemic candidiasis; candidemia; candiduria; Candida albicans; non-albicans Candida; children; BLOOD-STREAM INFECTIONS; INTENSIVE-CARE UNITS; SPECIES DISTRIBUTION; ANTIFUNGAL SUSCEPTIBILITY; NATIONWIDE SURVEILLANCE; RISK-FACTORS; HOSPITALS; FLUCONAZOLE; POPULATION; FUNGEMIA